EEG-Based Brain-Machine Interface (BMI) for Controlling Mobile Robots: The Trend of Prior Studies - Murali Krishnan; Muralindran Mariappan (Volume 3, Issue 2, 2015)
Recently, a novel method created on thought based brain signal and it has been technologically advanced rapidly. The Brain control system is a rapidly emerging multidisciplinary study area which has perceived remarkable achievement over the past few years. In this paper, we review the background, feature extraction and classification algorithms used to design the Electroencephalography (EEG) based Brain-Machine Interface (BMI) to control the mobile robots.